Monopolizing the Master : Henry James and the politics of modern literary scholarship - Anesko, Michael (Stanford University Press, 2012)
Henry James defied posterity to disturb his bones: he was adamant that his legacy be based exclusively on his publications and that his private life and writings remain forever private. Despite this, almost immediately after his death in 1916 an intense struggle began among his family and his literary disciples to control his posthumous reputation, a struggle that was continued by later generations of critics and biographers. Monopolizing the Master gives a blow-by-blow account of this conflict, which aroused intense feelings of jealousy, suspicion, and proprietorship among those who claimed.